(untitled) (Research, Society and Development, 2020)
Bromeliaceae comprises a numerous group of plant species that have a vast biological potential, still little studied. In view of this, this study aimed to identify the scientific evidence about the biological potential of plants of the Bromeliaceae family and the species Encholirium spectabile Mart. ex Schult. & Schult. f. It is an integrative literature review in the Scopus, Scifinder, Medline, Web of Science databases and in the electronic libraries Sciencedirect and Scielo, in the period between 2013 and 2019. As a result, a total of 18 articles were selected, after application of the inclusion and exclusion criteria. Of the studies found, those that were identified in greater quantity are related to antimicrobial activity. Bromelia pinguin, Bromelia laciniosa, Neoglaziovia variegata, Encholirium spectabile, among other species, showed microbicidal activity against Gram-positive and Gram-negative bacteria, including Staphylococcus aureus, Staphylococcus epidermidis, Pseudomonas aeruginosa and Escherichia coli. Some studies have also demonstrated the anti-inflammatory activity of Bromelia balansae, the antiulcerogenic activity of Ananas ananassoides and the anti-rheumatic and antioxidant properties of Encholirium spectabile. In addition to the aforementioned properties, the photoprotective, antinociceptive, antiophidic, anticoagulant potential, among others, were identified, and the relationship between these activities and the presence of secondary metabolites was established. From searches in the literature, it was possible to find numerous researches that support the use and continuous study of medicinal plants as an alternative method to current medicinal practices. With this study, we want to contribute to the expansion of knowledge about the biological potential of the Bromeliaceae family.